2004
DOI: 10.1111/j.0906-6705.2004.00164.x
|View full text |Cite
|
Sign up to set email alerts
|

The production of collagen and the activity of mast‐cell chymase increase in human skin after irradiation therapy

Abstract: Fibrosis is a common complication of radiotherapy. The pathogenesis of radiation-induced fibrosis is not known in detail. There is increasing evidence to suggest that mast cells contribute to various fibrotic conditions. Several mast-cell mediators have been proposed to have a role in fibrogenesis. Tryptase and chymase, the predominant proteins in mast cells, have been shown to induce fibroblast proliferation and collagen synthesis in vitro. In order to explore the role of mast cells in irradiation-induced fib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
35
0
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 57 publications
(38 citation statements)
references
References 53 publications
1
35
0
2
Order By: Relevance
“…This process can be a result of the release of a series of fibrogenic cytokines such as platelet derived growth factor (PDGF), tumor necrosis factor (TnF-α) and basic fibroblast growth factor (b-FGF). In addition, the main components in mast cell granules are the tryptase and chymase enzymes that have been proven to stimulate and induce the proliferation of fibroblasts and type 1 collagen synthesis (3,12).…”
Section: Resultsmentioning
confidence: 99%
“…This process can be a result of the release of a series of fibrogenic cytokines such as platelet derived growth factor (PDGF), tumor necrosis factor (TnF-α) and basic fibroblast growth factor (b-FGF). In addition, the main components in mast cell granules are the tryptase and chymase enzymes that have been proven to stimulate and induce the proliferation of fibroblasts and type 1 collagen synthesis (3,12).…”
Section: Resultsmentioning
confidence: 99%
“…Thus, although no published studies that compared changes in the tongue with changes in the heart of CD were found, we believed that in the cases analyzed, the tongue lesions caused by T. cruzi were older than the cardiac lesions and were at a more advanced stage of the tissue repair process, justifying the greater collagen density in the lingual muscles of Correlation between collagen intensity and MCH density in the myocardium of the chagasic patient group the chagasic patient group. Moreover, as a higher MCT density was found in lingual muscles than in the myocardium, we believed that these cells could have contributed to the fibrogenesis in the inflammatory process, since there is a study showing that tryptase-positive mast cells and fibroblasts are closely associated (Riekki et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…[33] This was attributed due to the presence of a number of chemical mediators including histamines, proteases, chymase and tryptase within the secretory granules of the mast cells. [34,35,36] In addition to the above, mast cells were associated with increased migration and proliferation of fibroblasts [37] as well as affecting the fibroblast's functional behaviour through releasing fibrogenic cytokines including platelet-derived growth factor (PDGF), tumor necrosis factor-a (TNF-a), and basic fibroblast growth factor (b-FGF). [38,39] The last (b-FGF) was specifically associated with epulis formation.…”
Section: Hande X 100mentioning
confidence: 99%